Examining associations between social vulnerability and maternal morbidity among a multicentre cohort of pregnancies complicated by placenta accreta spectrum disorder in New York City - Nicola Francesco Tavella; Henri Mitchell Rosenberg; Alexandra Mills; Thomas Owens; Lois Brustman; Georgios Doulaveris; Shoshana Haberman; Meghana Limaye; Teresa Janevic; Rebecca Hope Jessel; Angela Teresa Bianco (BMJ Publishing Group, 2024)
Background Placenta accreta spectrum (PAS) disorder is a source of severe obstetric morbidity and mortality worldwide. The objective of this paper was to evaluate the potential relationship between social vulnerability and severe maternal morbidity in a cohort of patients delivering a pregnancy complicated by PAS.Methods A retrospective review of 323 deliveries at three academic medical institutions between January 2013 and June 2022 was included in the analyses. Patients were those with a histopathologically confirmed case of PAS. The composite morbidity outcome included such maternal complications as mechanical ventilation, injury to organs and transfusion of 4+units of red blood cells. Social vulnerability was measured by assigning subjects a value of the Childhood Opportunity Index based on their home zip code. Logistic regression models were employed and adjusted for potential confounders.Results 73% of our sample experienced composite severe maternal morbidity at the time of their delivery. There were no statistically significant associations between social vulnerability and severe surgical morbidity, either as a composite or individually, within the multivariate regression models.Conclusion Our results do not support the hypothesis that social vulnerability is associated with severe maternal morbidity in deliveries complicated by PAS. The present study suggests that the relationship between social vulnerability and obstetrical surgical morbidity is more complicated than can be assessed by the present linear regression models.